The defense industry in Brazil: Characteristics and involvement of supplier firms - Flávia de Holanda Schmidt Squeff; Lucas Rocha Soares de Assis (Institute for Applied Economic Research (ipea), 2015)
Over the last decade, the defense industry has obtained relevance on Brazilian public policies. Departing from the premise that the success of this process requires not only that the Armed Forces have modern equipment and skilled military to operate them, but also that the country retains the technological expertise and acquire the conditions for constant arms improvement and introduction of innovations, this text offers information on defense procurement recently undertaken and analyzes selected characteristics of suppliers. The results indicate that the value of contracts obtained by firms was positively associated with characteristics related to the establishment of a sustainable and competitive DIB.
Keywords: H56; H57; L10; 330; defense industry; public procurement; defense procurement